Analysis and application of modern supply chain system in China - Lihua Chen; Yi Lu; Rui Zhao (Modern Supply Chain Research and Applications, 2019)
Purpose The purpose of this paper is make a significant contribution to the supply chain knowledge system through research on modern supply chain system in China, providing guidance for theoretical research such as methodology of dynamic resource allocation and application of innovative small- and middle-sized service system in the supply chain. Design/methodology/approach The paper uses structural analysis of Chinese competitive advantage, and it applies comparative analysis of supply chain models in China, the USA and Japan through the factor disintegration of trading environment. Findings China's supply chain model has virtual scale and virtual capabilities. The relationship with suppliers is more dynamic. The requirements for resolving uncertainty are higher. Business transfer is more frequent. Research limitations/implications Researchers are encouraged to propose the specific supply chain models in China further with the game theory, auction theory, etc. Practical implications It provides advice for government policy making and gives Chinese enterprises guidance to improve operation management. Originality/value This paper specifically analyzes characteristics of China supply chain and gives enlightenment for supply chain innovation.
Keywords: 650; Agglomeration effect; Scale effect; Industrialization service system; Supply chain in China; Virtual capability